TRPV4 and KRAS and FGFR1 gain-of-function mutations drive giant cell lesions of the jaw - Carolina Cavalieri Gomes (Nature Portfolio, 2018)
Giant cell lesions of the jaw (GCLJ) are debilitating benign tumors of unclear origin. The authors identify driver recurrent somatic mutations in TRPV4, KRAS and FGFR1 and show they converge on aberrant activation of the MAPK pathway. Their findings extend the spectrum of TRPV4 channelopathies and provide rationale for targeted therapies at the bedside in GCLJ.